Safety and efficacy of TRIANGLE operation applied in pancreatic surgery: a protocol of the systematic review and meta-analysis - Wei, Kongyuan; Klotz, Rosa; Kalkum, Eva; Holze, Magdalena; Probst, Pascal; Hackert, Thilo (BMJ open, 2022)
Background Pancreatic surgery is regarded as the only curative treatment for pancreatic cancer (PC). As the neoadjuvant therapy is applied widely nowadays, the proportion of patients with PC undergoing surgery also with locally advanced tumour findings has increased accordingly. Especially in these situations, a radical resection of all tumour tissues is challenging. A novel surgical strategy has been introduced recently to achieve this aim, namely the TRIANGLE operation which comprises the radical resection of all nerve and lymphatic tissue between coeliac artery, superior mesenteric artery and mesenteric-portal axis without including extended lymphadenectomy outside this area. Due to currently published studies, Triangle Operation is a safe and feasible procedure. However, this has not been systematically analysed to date. This systematic review and meta-analysis aim to evaluate surgical and postoperative outcomes of Triangle Operation in pancreatic surgery. - Methods and analysis Pubmed, Web of Science and Cochrane Central Register of Controlled Trials in the Cochrane Library will be searched from inception until 31 December 2022. This study will include all articles comparing Triangle Operation versus non-Triangle Operation in pancreatic surgery to assess outcomes. The primary endpoints will be R0 resection rate and 1-year overall survival. The secondary endpoints will be delayed gastric emptying, postoperative pancreatic fistula, post pancreatectomy haemorrhages and reoperation incidence, overall complications, mortality and 3-year overall survival. The study selection, study quality assessment, data extraction and critical appraisal will be carried out by two reviewers. Inter-reviewer disagreements will be evaluated by discussion with a third reviewer. Besides, a subgroup analysis will be conducted focused on robotic surgery, laparoscopic surgery and open surgery in detail. Additionally, the Grading of Recommendations, Assessment, Development and Evaluations framework will be performed to evaluate the strength of evidence. - Ethics and dissemination This systematic review and meta-analysis will not require ethical approval. Results will be published in a peer-reviewed scientific journal. - PROSPERO registration number CRD42021234721.
Gesehen am 21.10.2022